Latitude and chlorophyll a density drive the distribution of carbohydrate‐active enzymes in the planktonic microbial fraction of the epipelagic zone. Issue 5 (4th August 2020) - Doane, Michael; Haggerty, John Matthew; da Silva Lopes, Cleanto Rodrigo; Yates, Peter; Edwards, Rob; Dinsdale, Elizabeth; Lopes, Fabyano Alvares Cardoso; Bruce, Thiago
Summary: Microbes drive the majority of the global carbon cycle. The effect of environmental conditions on selecting microbial functional diversity is well established, and recent studies have revealed the effects of geographic distances on selecting the functional components of marine microbial communities. Our study is the first attempt at establishing the effects of environmental factors on driving the marine carbohydrate‐active enzyme (CAZyme) distribution. We characterized the diversity of CAZyme genes and investigated the correlations between their distributions and biogeographic parameters (latitude, longitude, distance from the equator, site depth, water depth, chlorophyll density, salinity and temperature). Therefore, we accessed a subset of surface water samples (38 metagenomes) from the Global Ocean Sampling project. Only chlorophyll and latitude altered the distribution patterns of CAZymes, revealing the existence of two latitudinal gradients (positive and negative) of marine CAZyme abundance. Considering the importance of carbohydrates in microbial life, characterization of the spatial patterns of the genetic repertoire involved in carbohydrate metabolism represents an important step in improving our understanding of the metabolic strategies associated with the microbial marine carbon cycle and their effects on the productivity of marine ecosystems.